Karakteristik Modal Sosial pada Kelompok Pengrajin Batik Kota Semarang - Yoshe Rezky Adhitama Mywa Putri; Prihadi Nugroho (Diponegoro University, 2020)
Batik is one of many small and medium enterprises (SMEs) which is being developed in Semarang City. However, location becomes the weakness of the batik industry in Semarang City. The scattered location of batik craftpersons makes public did not concern to the existence of batik Semarang. Therefore, FEDEP (Forum Economic Development and Employement Promotion) of Semarang City has formed a Semarang’s Batik Craftperson Group since 2006. The existence of this group has triggered the social capital among the craftperson, so they can interact and cooperate to improve their business productivity. This study aims to explain how the characteristics of social capital on Batik Craftperson Group in Semarang City. The method used sequential mix method with data unit is 31 members of Semarang’s Batik Craftperson Group. Trust, norms, and networks have their own characteristics to improve the business through interactions and communications. These three components also play a role in group management to make strategies, allocations, cooperations, and group activities. The characteristics of social capital on Batik Craftperson Group is expected to prove that so many factors that can develop SMEs, not only location but also the social capital of its business actors.